Isolation and identification of escherichia coli in well water located in Garut Regency - Sugiah Sugiah; Gina Nafsa Mutmaina; Mamay Mamay; Astari Nurisani (Institute of Computer Science (IOCS), 2023)
Water is one of the most important needs for daily life, especially well water. In the Garut district area well water is used for daily activities ranging from washing, drinking, bathing, ablution to being used for drinking water consumption. This study aims to isolate and identify well water from 10 villages located in the Garut Regency. Sampling was done using purposive sampling method. The test was followed by a presumptive test using Lactose Broth (LB), a reinforcing test using 2% BGLB media and a complementary test consisting of EMB agar media and biochemical tests. The results showed that of the 10 well water samples, 7 met the requirements of proper water quality and 3 did not meet the requirements of clean water with MPN values from three villages, namely Kampung Tanjung kamuning 200/ml, Kampung salaawi 241/100ml and Kampung Cipepe 241/100ml. EMB agar media is characterized by the formation of a metallic green color with black spots colonies and biochemical tests that show the well water has been contaminated with Escherichia coli bacteria.